Business Continuity and Risk Mitigation in the Pharmaceutical Industry: Strengthening Supply Chains for Pandemic Preparedness (International Journal of Scientific Research and Management (IJSRM), 2025)
The COVID-19 pandemic disclosed critical weaknesses in pharmaceutical supply systems which demonstrate the requirement for strong continuous business operations planning methods combined with risk management measures to sustain uninterrupted delivery of essential medical products. The pharmaceutical industry needs active strategic planning to develop resilient supply chains which will ensure operational stability in times of emergencies because global health crises are growing more unpredictable. This article investigates the main supply chain obstacles which pharmaceutical industry encounters during pandemics concerning raw material sourcing problems and production constraints as well as regulatory burdens and distribution delays. The article presents essential supply chain enhancement approaches which include multiple supplier network dispersion and real-time tracking support delivered through artificial intelligence (AI) and blockchain technology and established stockpiling strategies and flexible manufacturing protocols to achieve rapid production acceleration. This article evaluates the function of public-private alliances together with regulatory bodies that enhance industry readiness against future pandemic events.